1989
DOI: 10.1182/blood.v74.2.798.798
|View full text |Cite
|
Sign up to set email alerts
|

A possible autocrine role for interleukin-6 in two lymphoma cell lines

Abstract: Interleukin-6 (IL-6) is a growth factor with diverse biologic activity. Originally described as a T-cell product that enhances immunoglobulin (Ig) secretion in antigen-stimulated B cells, it also affects the growth of T cells, plasmacytomas, hybridomas, and hematopoietic stem cells. We report the expression and secretion of IL-6 by two lymphoma cell lines, OCI-LY3 and OCI-LY12. Addition of recombinant IL-6 stimulated their growth, whereas addition of polyclonal anti- recombinant IL-6 (anti-rIL-6) had a marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…A possible autocrine role for IL-6 was also reported in non-Hodgkins lymphomas, chronic lymphocytic leukemias and acute myeloid leukemias [79, IL-6 was also demonstrated to be an autocrine growth factor for EBV-transformed B cell lines [89] and expression of an exogenous IL-6 gene in these B cell lines conferred growth advantage and in vivo tumorigenicity [90]. However, it has been controversial whether all myeloma cells actually produce IL-6, because only some myeloma cell lines were found to produce IL-6 [76,91-931, and bone marrow-adherent cells (rather than bone marrow nonadherent cell populations [86][87][88].…”
Section: Il-6 Is a Growth Factor For Plasmacytoma/myelomamentioning
confidence: 99%
“…A possible autocrine role for IL-6 was also reported in non-Hodgkins lymphomas, chronic lymphocytic leukemias and acute myeloid leukemias [79, IL-6 was also demonstrated to be an autocrine growth factor for EBV-transformed B cell lines [89] and expression of an exogenous IL-6 gene in these B cell lines conferred growth advantage and in vivo tumorigenicity [90]. However, it has been controversial whether all myeloma cells actually produce IL-6, because only some myeloma cell lines were found to produce IL-6 [76,91-931, and bone marrow-adherent cells (rather than bone marrow nonadherent cell populations [86][87][88].…”
Section: Il-6 Is a Growth Factor For Plasmacytoma/myelomamentioning
confidence: 99%
“…Further analysis revealed that this cell line produced IL-6 protein and showed a n autocrine pattern 0 1991 WILEY-LISS, INC of growth control by IL-6. Rearrangement of the IL-6 gene did not account for the expression of IL-6 as Southern blot analysis of the IL-6 gene revealed that the OCI-LY3 cell line had a germline configuration of the IL-6 gene (Yee et al, 1989).…”
mentioning
confidence: 97%
“…OCI-LY13.1, a T-cell line of class I, does not express the message for IL-6. In contrast, the class 111 B-cell line OCI-LY3 expresses abundant IL-6 message and biologically active protein (Yee et al, 1989). Both cell lines are maintained in 10% human plasma in Iscove's medium.…”
mentioning
confidence: 99%
“…At present, nothing is known about an autocrine stimulation by IL-6 in malignant BL cells but the finding that IL-6 mRNA was detected in one of two investigated BL preparations (Freeman et al, 1989) supports this assumption. In two lymphoma cell lines of T-or B-cell origin, other than BL, IL-6 could be detected as an autocrine growth factor (Yee et al, 1989).…”
mentioning
confidence: 98%